Implementing green education of urban families: An action research project in Beijing, China. Issue 1 (March 2020) - Hou, Xin; Ma, Yuna; Wu, Yang; Wang, Weiwei
Crises in food safety have attracted increased public attention in many countries, typically posing serious threats to public health and causing potential economic, social, and environmental damage. This research applied a green social work framework and developed a family-based and child-centered education model in a Chinese urban context. The green educational model engaged practitioners in a participatory and cooperative learning process to explore practical solutions for food safety that had social and environmental value. Applying action research, this program engaged participant families in extended ways of knowing in educational activities, through which to enhance their emotional connection with the natural environment, and develop critical knowing and reflective action. The program generated useful insights for green social work intervention and public education to improve environmental justice and providing lessons about action research as a method of engagement for social workers.